Successful Resuscitation of a Patient with Ventricular Fibrillation due to Hypomagnesemia under Cetuximab Therapy - Kordelas, L.; Bauer, S.; Schuler, M.; Beelen, D. W.; Gauler, T. C. (TumorDiagnostik & Therapie, 2014)
Introduction: Cetuximab is a monoclonal antibody against the epidermal growth factor (EGF) receptor and is commonly used against colorectal carcinoma and squamous cell carcinomas of the head and neck. There are indications on a magnesium wasting syndrome in patients treated with cetuximab.Patients and Methods: We here report on a patient who developed ventricular fibrillation most likely due to hypomagnesemia under cetuximab therapy and who was successfully resuscitated.Results/Conclusion: Hypomagnesemia under cetuximab therapy is a potentially life-threatening side-effect. Magnesium levels should be regularly monitored under cetuximab therapy and – if required – magnesium should be supplemented.
Keywords: resuscitation; ventricular fibrillation; hypomagnesemia; Cetuximab